The Potential of Seagrass Ecotourism as an Indicator of Conservation in the Coastal Waters of East Lombok - Abdul Syukur; Agil Al Idrus; Lalu Zulkifli; Mahrus Mahrus (Pascasarjana, Mataram University, 2020)
The East Lombok coast was developed for fisheries and tourism. The fishery aspect that is being developed is marine cultivation and has contributed as a source of livelihood for local communities and from the social aspect, it functions to maintain the safety and comfort of the environment. Besides, from an ecological aspect, it has benefits in preventing damage to marine ecosystems due to the use of tools and materials that are not environmentally friendly. The utilization model of the marine environment is still traditional which is oriented only to goods and not to environmental services. On the other hand, the development of nature tourism is becoming superior in the southern coastal area of Lombok Island. It spreads the seagrass ecosystem in the coastal area of Lombok across all tourist sites. However, the utilization is only from products such as fish and marine biota which have economic value. Therefore, it is necessary to innovate the utilization of the ecosystem services aspect of the field as a natural tourist attraction with the concept of ecotourism. The concept of ecotourism is a utilization model that does not interfere with natural systems or ecological systems. The uniqueness of the seagrass ecosystem with other ecosystems is its relationship with the local community tradition called